Photodegradation of microplastics - Catarí, Edgar; Ramón Vargas, Franklin; Celeste Angulo, Beatriz (Ingeniería Química y Desarrollo, 2024)
The environmental degradation processes that plastics suffer in the environment are described, thus generating minor fragments known as microplastics. The various chemical mechanisms by which these microplastics can be decomposed by the effect of light and environmental oxygen (photo-oxidation of polymers) will be described. Emphasis is placed on the role of photochemistry in the degradation processes of microplastics until they become compounds that are harmless to the environment, that is, until they are mineralized (HCO3, CO2, etc.). Some advances in the development of heterogeneous photocatalysts based on transition metals used in the degradation of microplastics are also presented, including a particular and interesting automated microrobot photocatalyst system based on BiVO4/Fe3O4, which has proven to be effective. in the degradation of polylactic acid (PLA), polycaprolactone (PCL), polyethylene terephthalate (PET) and polypropylene (PP) microplastics on a laboratory scale.
Keywords: Photodegradation; microplastics; photochemistry; polymere; photooxidation